Lead bioaccumulation in herbivorous insects and parasitoids reared on plants grown in lead-contaminated soil under field conditions - Morales-Silva, Tiago (2024)
We investigated the lead (Pb) bioaccumulation in herbivorous insects and parasitoids on kale plants (Brassica oleracea var. acephala) cultivated in soils experimentally contaminated. We cultivated kale in soil with lead nitrate concentrations of 0 (control), 144, 360, and 600 mg/Kg of soil, representing permissible levels for Brazilian soils. The plants were kept in an open greenhouse to allow the natural colonization by insects under field conditions. We collected insects through direct removal or trap bags. Dried samples of leaves, herbivorous sap-sucking and chewing insects, and their respective parasitoids were analyzed utilizing ICP-OES to determine Pb concentrations. Pb was transferred in this system, with insects showing higher Pb content than leaves, and the highest values being found in parasitoids, which exhibited the highest levels ever recorded, even though our foliar Pb levels were lower than those in laboratory assays conducted up to then. These results indicate Pb biomagnification. We discuss Pb bioaccumulation effects on herbivores and parasitoids, comparing them with laboratory studies. We provide unprecedented insights into heavy metal bioaccumulation in field herbivorous insects and parasitoids.